Persistently Increased Systemic ACE2 Activity Is Associated With an Increased Inflammatory Response in Smokers With COVID-19 - Kaur, Gagandeep; Yogeswaran, Shaiesh; Muthumalage, Thivanka; Rahman, Irfan (Frontiers in Physiology, 2021)
Background: Tobacco smoking is known to be involved in the pathogenesis of several cardiopulmonary diseases. Additionally, smokers are highly susceptible to infectious agents due to weakened immunity. However, the progression of lung injury based on SARS-CoV-2-mediated COVID-19 pathogenesis amongst smokers and those with pre-existing pulmonary diseases is not known. We determined the systemic levels and activity of COVID-19 associated proteins, cytokine/chemokines, and lipid mediators (lipidomics) amongst COVID-19 patients with and without a history of smoking to understand the underlying susceptible factor in the pathogenesis of COVID-19. Methods: We obtained serum from healthy (CoV-), COVID-19 positive (CoV+), and COVID-19 recovered (CoV Rec) subjects with and without a history of smoking. We conducted a Luminex multiplex assay (cytokine levels), LC/MS (eicosanoids or oxylipin panel), and ACE2 enzymatic activity assays on the serum samples to determine the systemic changes in COVID-19 patients. Results: On comparing the levels of serum ACE2 amongst COVID-19 (positive and recovered) patients and healthy controls, we found a pronounced increase in serum ACE2 levels in patients with COVID-19 infection. Furthermore, ACE2 enzyme activity was significantly increased amongst COVID-19 patients with a smoking history. Also, we analyzed the levels of Angiotensin 1-7 (Ang1-7) peptide, the product of enzymatic action of ACE2, in the serum samples. We found significantly high levels of Ang1-7 in the serum of both CoV+ and CoV Rec patients. Our data further demonstrated a smoking-induced increase in serum furin and inflammatory cytokine [IFN(p=0.0836), Eotaxin (p<0.05), MCP-1 (p<0.05), and IL-9 (p=0.0991)] levels in COVID-19 patients as compared to non-smoking controls. Overall, our results show that smoking adversely affects the levels of systemic inflammatory markers and COVID-19 associated proteins, thus suggesting that COVID-19 infection may have severe outcomes amongst smokers.